1987
DOI: 10.1177/0310057x8701500204
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Formulation and Addition of Adrenaline to Cocaine for Haemostasis in Intranasal Surgery

Abstract: Twenty patients presenting for submucous resection of the nasal septum under general anaesthesia were randomly allocated to four groups to receive either 1.0 ml 25% cocaine HCI in paraffin paste, 1.0 m125% cocaine HCI combined with 0.1% adrenaline in paraffin paste, 4.0 ml aqueous 4% cocaine HCI combined with 0.050/0 adrenaline or 4.0 ml aqueous 4% cocaine HCI on ribbon gauze applied to the nasal mucosa. Mean intraoperative blood loss was significantly decreased when the 25% cocaine 0.1% adrenaline combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…There was no difference in intraoperative bleeding or surgical field visualization amongst the studies reported in the literature [ 7 , 26 28 ]. Further, none of the trials in the literature demonstrate an increased risk of cardiovascular morbidity or mortality associated with the use of intranasal cocaine which is in keeping with the results of our study [ 2 , 25 30 ]. The reports of adverse cardiovascular events associated with the use of intranasal cocaine are from case studies [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…There was no difference in intraoperative bleeding or surgical field visualization amongst the studies reported in the literature [ 7 , 26 28 ]. Further, none of the trials in the literature demonstrate an increased risk of cardiovascular morbidity or mortality associated with the use of intranasal cocaine which is in keeping with the results of our study [ 2 , 25 30 ]. The reports of adverse cardiovascular events associated with the use of intranasal cocaine are from case studies [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…Several trials have been conducted on patients undergoing sinonasal surgery using topical cocaine compared to other agents. The primary outcomes of these studies include pain perception [21,22], plasma absorption of intranasal cocaine [23][24][25], surgical field visualization and intraoperative bleeding [7,[26][27][28], and adverse events (including cardiovascular changes, electrocardiogram changes, cardiovascular events and mortality) [2,[25][26][27][28][29][30]. There was no difference in intraoperative bleeding or surgical field visualization amongst the studies reported in the literature [7,[26][27][28].…”
Section: Plos Onementioning
confidence: 99%
“…This is thought to improve the operative eld by improving both visualization and decreasing bleeding during surgery. 4,5 Much has been written on the use of different materials for post-operative packing for both stenting and haemostasis 2,3,6 but little on the effects of pre-operative packing.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of adrenaline to cocaine to limit systemic absorption and improve operating conditions and haemostasis has remained controversial. Lips et al showed that, although the addition of adrenaline to 4% cocaine solution significantly reduced systemic absorption of cocaine, this effect was not seen when adrenaline was added to cocaine paste 6. Cocaine paste improved operating conditions, however, and reduced blood loss.…”
Section: Discussionmentioning
confidence: 99%